ANALISIS YURIDIS ATAS PERJANJIAN PERKAWINAN DITINJAU DARI UNDANG-UNDANG NO.1 TAHUN 1974 TENTANG PERKAWINAN DAN IMPLIKASI PUTUSAN MK NO.69/PUU-XIII/2015 - Wisda Rauyani Efa Rahmatika; Akhmad Khisni (Jurnal Akta, 2017)
Act No. 1 of 1974 on Marriage in Article 29, which explains that at the time the marriage took place before the bride who wants to do a wedding in which the consent of both parties must make a marriage agreement in writing beforehand. However, the fact that an Indonesian citizen who is married to foreign citizens who perform mixed marriages, filed a petition to the Constitutional Court relating to Article 29 of the Marriage Act. Indonesian citizen that feels aggrieved because when they wanted to buy a flat can not be done because the rejection of purchase from the developer because the buyer is married to citizens of foreign, which in Article 35 of the Marriage Law that property acquired during the marriage become community property, then in Article 21 UUPA that only citizens of Indonesia who can both have property rights. Therefore, the applicant felt disappointed, harmed and human rights have been usurped by their rules.The formulation of the problem in this research are: 1) What about the implications of the Constitutional Court. No. 69 / PUU-XIII / 2015 against the marriage contract stipulated in Law No.1 of 1974 on Marriage? 2) How is the implementation of the agreement is a marriage in the Act No.1 of 1974 on Marriage after the decision of the Court. 69 / PUU-XIII / 2015? 3) how the barriers and solutions in implementing the agreement is a marriage in Act 1 of 1974 on Marriage Following the Ruling of the Constitutional Court. 69 / PUU-XIII / 2015?The method used in this thesis is a normative juridical legal research. Ie normative legal research legal research conducted by reviewing the materials of the legislation and other materials derived from the literature.The results of this study are: 1) That the decision of the Court No.69 / PUU-XIII / 2015 are final, binding, and binding on all the parties, both litigants, agency, government law and notary 2) that the manufacturing operations after the marriage covenant decision of the Court. 69 / PUU-XIII / 2015, namely, which initially manufacture the marriage contract according to Law No.1 of 1974 on Marriage made before the marriage is done but with the Constitutional Court's decision No.69 / PUU-XIII / 2015 the agreement is made before the marriage dapan marriage took place or after held 3) in the manufacture of the marriage covenant are obstacles that happen is if the parties want to make the marriage covenant are lying or data used by the parties do not fit their therefore a Notary should be more careful and cautious associated with the those who want to make arrangements.Keywords: Marital Agreement, Decision of the Constitutional Court, Notary